The Standardization of Acupuncture Treatment for Radiation-Induced Xerostomia： A Literature Review - 李凌鑫 田光 何竟 (Chinese journal of integrative medicine, 2016)
Objective： To assess the relative standardization of acupuncture protocols for radiation-induced xerostomia. Methods： A literature search was carried out up to November 10, 2012 in the databases PubMed/ MEDLINE, EMBASE and China National Knowledge Infrastruction with the terms： radiation-induced xerostomia, acupuncture, acupuncture treatment, and acupuncture therapy. Five ancient Chinese classic acupuncture works were also reviewed with the keywords ＂dry mouth, thirst, dry tongue, dry eyes and dry lips＂ to search the effective acupuncture points for dry mouth-associated symptoms in ancient China. Results： Twenty-two full-text articles relevant to acupuncture treatment for radiation-induced xerostomia were included and a total of 48 acupuncture points were searched in the 5 ancient Chinese classic acupuncture works, in which the most commonly used points were Chengjiang （CV24）, Shuigou （GV 26）, Duiduan （GV 27）, Jinjin （EX-HN 12）, and Yuye （EX-HN 13） on head and neck, Sanjian （LI 3）, Shangyang （LI 1）, Shaoshang （LU 11）, Shaoze （SI 1）, Xialian （LI 8） on hand, Fuliu （KI 7）, Dazhong （KI 4）, Zuqiaoyin （GB 44）, Taichong （LR 3）, Zhaohai （KI 6） on foot, Burong （ST 19）, Zhangmen （LR 13）, Tiantu （CV 22）, Qimen （LR 14） on abdomen, Feishu （BL 13）, Danshu （BL 19）, Xiaochaogshu （BL 27）, Ganshu （BL 18） on back, Shenmen （TF 4）, Shen （CO10, Kidney）, Yidan （CO11, Pancreas） and Pi （CO13, Spleen） on ear. Conclusion： There were considerable heterogeneities in the current acupuncture treatment protocols for radiation-induced xerostomia. Based on the results of the review and the personal perspectives, the authors provide a recommendation for manual acupuncture protocols in treating radiationinduced xerostomia patients with head and neck cancer.